Evaluation of electrochemical impedance properties of anti-corrosion films by Arc thermal metal spraying method - Choe, H.; Lee, H.; Ismail, Mohamed; Hussin, M. (Electrochemical Science Group, 2015)
Arc thermal metal spraying method (ATMSM) provides proven long term protective coating systems using zinc, aluminum and their alloys for steel structure in a marine environment. This paper focused on studying the effect of spraying metal type, and presence or absence of pore sealing agent on impedance properties of Arc Thermal Metal Spraying (ATMS) film. The results showed that the impedance property of ATMS film was significantly varied depending on whether the metal type applied pertains to the Zn or Al series. Also, the reaction system between the interface of ATMS film and electrolyte was analyzed by interpreting its equivalent circuit. Consequently, the representative equivalent circuits were presented as models to be applied on ATMS film according to metal type (Zn series, Al series) and the presence or absence of a pore sealing agent.